Cultural Tourists' Satisfaction from a Leisure Experience Perspective: An Empirical Study in China. Issue 3 (2nd July 2020) - Xu, Yuchen; Zhang, Haizhou; Lu, Lin; Zha, Xiaoli
ABSTRACT: This study aims to examine cultural tourists' leisure experience characteristics and their relationship with satisfaction. Using a sample of cultural tourists (n = 850) in the Huizhou Cultural and Ecological Protection Experimental Area (HCEPEA) collected via questionnaire surveys. Of the overall samples, 215 was used for scale development and the rest was used for structural model evaluation. The results showed that both the measurement and structural models exhibited acceptable model fit indices. Nine 'leisure experience characteristics' factor was identified (i.e., sense of accomplishment, self-actualization, effort/persistency, self-enrichment, self-esteem/self- expression, socialization/social interaction, fun/enjoyment/freedom, recreation/regeneration, and self-reinvention). Overall, cultural tourists in HCEPEA showed higher levels of casual leisure/serious leisure characteristics than serious leisure characteristics, and serious leisure characteristics displayed a stronger influence on tourist satisfaction than casual leisure/serious leisure characteristics. These findings suggest cultural tourism is a form of tourism dominated by casual, and the more serious of leisure experience leads to the higher tourist satisfaction for cultural tourists.